Key considerations for ELISA-based quantification of diverse amyloid beta forms in murine brain homogenates - Metzendorf, Nicole G.; Sehlin, Dag; Hultqvist, Greta (Frontiers in Neuroscience, 2025)
Enzyme-Linked Immunosorbent Assay (ELISA) is a widely utilized method for quantifying amyloid beta (Aβ) levels in various biological samples, including brain homogenates. Aβ exist in multiple structural forms: monomers, soluble oligomers, protofibrils, and fibrils, each exhibiting distinct biochemical properties and degrees of neurotoxicity. Their toxic potential also varies by localization, whether intracellular, membrane-bound, or extracellular. Accurate detection and quantification of these diverse Aβ species and localizations are critical for understanding their roles in Alzheimer’s disease (AD) pathology. However, suboptimal ELISA configurations and misinterpretations of results can lead to misleading conclusions. This study highlights key considerations for optimizing ELISA protocols specifically for detecting distinct Aβ species and localizations, with a focus on applications in mouse brain tissue. We also provide guidance on antibody selection to improve selectivity and specificity of Aβ detection, ultimately enhancing the reliability and interpretability of ELISA-based Aβ measurements.